"Aussies love a bet": Gamblers discuss the social acceptance and cultural accommodation of gambling in Australia. (3rd October 2022) - Marko, Sarah; Thomas, Samantha; Pitt, Hannah; Daube, Mike
Abstract: Objective : This study aimed to explore regular gamblers' perceptions of the social acceptance and cultural accommodation of gambling in Australia, which are two dimensions of the normalisation of gambling. Methods : Qualitatively focused online survey with 363 adults in New South Wales and Victoria who gambled in a typical month. Open‐text responses about the link between gambling and Australian culture were interpreted using reflexive thematic analysis to construct themes from the data. Results : Gambling was perceived to be a culturally significant part of Australian life due to existing traditions, the perception that gambling was central to the Australian identity, and perceived economic benefits. Participants considered that gambling was a common and socially accepted activity that was embedded in the activities of social networks. Participants also stated that gambling products, venues and marketing were embedded in everyday environments, although some believed that the embedding of gambling in society was harmful. Conclusion and public health implications : This study demonstrated that regular gamblers largely viewed gambling as being a socially accepted and culturally accommodated activity in Australia. There is scope for governments to develop comprehensive programs to denormalise gambling, including learning from research, evidence and experience in other areas of public health.